MORBIDITY PROFILE OF WOMEN DURING PREGNANCY: A HOSPITAL RECORD BASED STUDY IN WESTERN UP - Singh, Ranjana; Chauhan, R; Nandan, Deoki; Singh, H; Gupta, S C; Bhatnagar, M (Indian Journal of Community Health, 2012)
Objective: To study the morbidity pattern and relationship of these morbidities with socio-economic and demographic factors. Material and method: Present study was conducted at the Saraswathi Institute of Medical Sciences,Hapur,(U.P.) among pregnant patients during the study period of one year. Data were analyzed using SPSS 16, using tabulation with percentage and Pearson's chi-square test was used for testing the crude associations. Results: In the present study a total of 338 pregnant women were included for the study material, out of which 67.46% of the antenatal women reported illness during antenatal period and majority 277(81.95%) of the pregnant women were anemic.Thecommon non-obstetric morbidities reported were gastrointestinal disorder (24.68%), genital tuberculosis (16.88%), renal & gall bladder disease (7.79%) and congenital anomaly (6.49%) ect. (ii) The obstetric morbidities included were pre-eclampsia(14.56%), urinary tract infection(9.71%), rupture of membrane(8.74%),hyperemesis gravidarum(9.22%)and abnormal presentation in (2.43%)patients . Conclusion: Maternal morbidity is notably high, although most of the common problems were not life-threatening. They are more likely to have marked influence on their wellbeing and health status in the long run. Most conditions could be addressed through provision of health promotion and preventive interventions.